World Geopolitical Competition in the Context of the Fourth Industrial Revolution - Konstantin V. Blokhin (RUDN Journal of Political Science, 2020)
Article analyzes predictive estimates and concepts presented by the Western intellectual community, regarding prospects for development of new trends in the global economy, caused by the fourth industrial revolution. Author draws on a variety of sources, including reports from US think tanks, works by representatives of global financial and technocratic elite, and works by American intellectuals. Methodological basis of the study is a theory of the world system of I. Wallerstein, which allows to identify dynamic and conflicting lines of interaction between two geopolitical centers of the world - the United States and China. Based on an analysis of current trends, modern experts predict revolutionary changes in modern technologies that can decisively affect socio-political stability, not only in Western countries, but in developing countries as well. Author shows that the new technological structure is changing not only sector structure of the economy, but also has a strong impact on employment. According to American analysts, new technologies can destabilize socio-political stability in any country, especially in countries where cheap labor is a traditional tool. Robotization and automation of production can become a competitive advantage of the United States and Western countries in competition with China. Article notes that Russia is only at the very beginning of technological revolution, behind big five leading countries. Overcoming its lag in the field of AI and robotics requires adoption of comprehensive measures of economic, scientific and political nature. Ignoring realities of technological progress is fraught with increase in threats to national security.